Immune checkpoint inhibitors for extensive-stage small-cell lung cancer: a network meta-analysis and cost-effectiveness analysis - Wen, Jiayu; Sun, Yuhao; Zhu, Yuxuan; Zhang, Jizhong; Tang, Qingshan; Zhu, Yifei; Wu, Nan; Liu, Zhixian; Liu, Xin; Xu, Silu; Wei, Jifu; Zhou, Guoren (Frontiers in Immunology, 2025)
BackgroundDespite the established efficacy of immune checkpoint inhibitors (ICIs) in combination with chemotherapy, with or without anti-angiogenic agents, for extensive-stage small-cell lung cancer (ES-SCLC), a comprehensive comparative assessment of these regimens remains lacking. This study aimed to systematically compare the safety, efficacy, and cost-effectiveness of currently available ICI combination regimens for ES-SCLC.MethodsPhase III randomized clinical trials (RCTs) published up to January 31, 2025, were retrieved from PubMed, Web of Science, Cochrane Library, ClinicalTrials.gov, European Union Clinical Trials Register, and the Chinese Clinical Trial Registry. A network meta-analysis (NMA) was performed to evaluate overall survival (OS), progression-free survival (PFS), objective response rate (ORR), ≥grade 3 adverse events (AEs), and surface under the cumulative ranking curve analysis (SUCRA) score. A cost-effectiveness analysis (CEA) was performed from the perspective of the Chinese healthcare system. A 10-year partitioned survival model (PSM) was used to estimate total costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios (ICERs).ResultsEight phase III RCTs were included. NMA demonstrated that benmelstobart and anlotinib plus chemotherapy ranked first in improving OS (HR = 0.81, 95% CI: 0.72–0.90), PFS (HR = 0.61, 95% CI: 0.55–0.67), and ORR (OR = 2.16, 95% CI: 1.43–3.27) compared to chemotherapy. Serplulimab plus chemotherapy ranked second in OS (HR = 0.82, 95% CI: 0.73–0.91) and PFS (HR = 0.73, 95% CI: 0.66–0.80). Regarding safety, tislelizumab plus chemotherapy exhibited the lowest incidence of ≥grade 3 AEs among eight ICI-based regimens. The CEA indicated that the ICERs of ICI-based regimens as compared to chemotherapy alone ranged from $45,360.61/QALY to $382,106.89/QALY, exceeding the Chinese willingness-to-pay (WTP) threshold ($40,500/QALY). However, tislelizumab plus chemotherapy emerged as relatively cost-effective, achieving the second-highest QALYs (1.27) and the second-lowest costs ($52,273.46). Sensitivity analyses affirmed the robustness of these findings.ConclusionsBenmelstobart and anlotinib plus chemotherapy demonstrated superior efficacy regarding OS, PFS, and ORR, while tislelizumab plus chemotherapy provided the most favorable safety profile among the evaluated ICI-based therapies. And none of the evaluated ICI-based regimens were cost-effective at the conventional WTP threshold. However, tislelizumab plus chemotherapy was the most cost-effective as the WTP threshold increased.